Nuclear proliferation : opposing viewpoints - Cozic, Charles P., 1957-; Swisher, Karin, 1966- (San Diego, CA : Greenhaven Press, 1992)
Presents differing opinions on the threat of nuclear proliferation, the need for arms control, the role of NATO, the elimination of nuclear weapons, and other related topics.
Includes bibliographical references (p. 225-227) and index.
Keywords: Nuclear nonproliferation -- Juvenile literature; Nuclear nonproliferation; Disarmament